Moderating effect of top management support on relationship between transformational leadership and project success - Syed Muhammad Javed Iqbal; Choi Sang Long; Goh Chin Fei; Syed Muhammad Labib Abdul Ba'ith Shah Bukhari (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Project success has remained the center of project management since long time. Continuous efforts are being indulged by various academicians and practitioners to find out the factors that contribute significantly toward project success. The authors edify the importance of project managers as transformational leaders in presence of top management support. This document investigates the interacting effect of top management support on relationship between project managers' transformational leadership and project success. The study covers a total of 125 project managers selected through systematic sampling technique by using mail survey method. PLS-SEM has been utilized to analyze the study data. The study concludes that project success can be enhanced through unfolding the relationships between project managers' transformational leadership and top management support. The study is pioneer to discuss these relationships particularly in a developing country. However, the study findings only rely on the higher education sector of Pakistan.
Keywords: 330; project success; project leadership; transformational leadership; top management support